2018
DOI: 10.2478/jvetres-2018-0048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated lipopolysaccharide treatment on growth performance, immune organ index, and blood parameters of Sprague-Dawley rats

Abstract: IntroductionThe study was designed to investigate the effects of repeated lipopolysaccharide (LPS) treatment on growth performance, lymphoid organ indexes, and blood cells in Sprague-Dawley rats.Material and MethodsForty healthy weaned Sprague-Dawley rats were randomly equally divided into LPS and control groups. Each rat in the LPS group was injected via the caudal vein with LPS (100 μg/kg b.w.) for 10 days, and the control group was treated with an equal volume of normal saline. On the 1st, 4th, 7th, and 10t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
7
12
2
Order By: Relevance
“…The present study focuses on elucidating promising protective roles of 6G against LPS-induced inflammation, oxidative stress, cognitive deficiency, and amyloidogenesis in rats. Treatment with LPS triggered a significant decrease in bw which is associated with toxic effect of the chemical, concordant with previous studies (Piirsalu et al, 2020;Zhong et al, 2018); however, the weight was significantly increased in the rats following the administration of 20 and 50 mg/kg bw 6G, and the restoration of body fitness by 6G at 20 and 50 mg/kg bw was associated with the health benefit of 6G during LPS administration. This finding is similar with our previous study (Ajayi et al, 2015), where we demonstrated that 6G improved the body weight of mice exposed to dextran sulfate sodium.…”
Section: Discussionsupporting
confidence: 91%
“…The present study focuses on elucidating promising protective roles of 6G against LPS-induced inflammation, oxidative stress, cognitive deficiency, and amyloidogenesis in rats. Treatment with LPS triggered a significant decrease in bw which is associated with toxic effect of the chemical, concordant with previous studies (Piirsalu et al, 2020;Zhong et al, 2018); however, the weight was significantly increased in the rats following the administration of 20 and 50 mg/kg bw 6G, and the restoration of body fitness by 6G at 20 and 50 mg/kg bw was associated with the health benefit of 6G during LPS administration. This finding is similar with our previous study (Ajayi et al, 2015), where we demonstrated that 6G improved the body weight of mice exposed to dextran sulfate sodium.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies also noted that LPS immune challenge caused growth reduction by depression in feed intake [14,20] which is inconsistent with the present study findings. The failure to observe the significant immune stimulation response as well as reduced growth performance in the present study may probably due to a single-dose LPS challenge since some studies noted that immune stimulation is activated by multiple low-dose LPS treatment Upadhaya et al [21] & Zhong et al [18] or it may be due to the route of LPS injection administration, presence of protein impurities in LPS preparation or variation in serotypes used in different studies [22,23]. Although E.coli LPS O111:B4 is the most frequently used in porcine research Williams et al [24]; however, the presence of protein impurities in those LPS preparations may affect the immune stimulation responses [25,26].…”
Section: Discussionmentioning
confidence: 63%
“…In contrast to the present finding, elevation in body temperature following the intraperitoneal administration of 100 µg/kg BW LPS in weaned pigs has been reported Wright et al [ 14 ] & Johnson & Bore [ 12 ]. In addition, increased plasma TNF-α concentration increased WBC counts and reduction in lymphocyte percentage has been reported with LPS challenge [ 17 , 18 ]. Similarly, LPS injection has been reported to induce the production of IgG [ 19 ].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we also found that LPS caused an increase in spleen weight in the sham-operated mice, and that SDV significantly alleviated the LPSinduced increase in spleen weight. In addition, it has been reported that repeated LPS (0.1 mg/kg/day for 10 days) administration increased spleen weight in rats 52 . Interestingly, we found positive correlations between IL-6 (or TNF-α) and spleen weight, indicating a close relationship between peripheral inflammation and spleen weight.…”
Section: Discussionmentioning
confidence: 96%